PERANCANGAN SISTEM INFORMASI DAN TEKNOLOGI INFORMASI ADMINISTRASI KEPENDUDUKAN PADA KELURAHAN CIKIWUL BEKASI - eko haryadi; Syafrianto Syafrianto; Anggie Anggraeni (JURNAL REKAYASA INFORMASI, 2020)
ABSTRACTS Basically the population administration system is part of the state administration system, which has an important role in the government to manage population data. Cikiwul Kelurahan is a government office in charge of managing, managing resources in village level government and has the obligation to administer population administration as a form of service to the community. The administrative data processing system in Cikiwul Kelurahan is still manual, which still uses Microsoft Office programs in data processing and archiving still using paper forms. Resulting in data storage that is still prone to data loss, ineffective population data search and reports that are still written in a ledger. By utilizing the development of information technology and information system, it is expected to be able to support the processing of administrative data in the Cikiwul District of Bekasi. A computerized system is the best solution, so that it can facilitate the process of recording, faster data retrieval, storage becomes easier to manage, and services to the population are more efficient and effective. Keywords: Design, Information Systems, Administration, Information Technology.